Peran Penyaluran Zakat Produktif Pada Lazisnu Belitung Sebagai Upaya Pemulihan Ekonomi Pasca Pandemi Covid-19 - Alawi, Lutfi (EJESH: Journal of Islamic Economics and Social, 2024)
ABSTRACT The Covid-19 pandemic that has hit in recent years has created new history for the economy. Economically, the Covid-19 pandemic has caused a significant economic contraction in Indonesia. To overcome this problem, namely by utilizing productive zakat to meet the basic needs of society and create a business that can be run sustainably. The aim of this research is to determine the role of zakat distribution to Lazisnu Belitung as a way of economic recovery after the Covid-19 pandemic. The research method used is a qualitative approach. The results of this research are that the role of Lazisnu Belitung in economic recovery after the Covid-19 pandemic is to distribute productive zakat funds which are expected by many mustahik parties to use the aid funds to fulfill their productive funding needs. Communities who receive productive zakat funds can maximize the potential of zakat funds for productive purposes and not only for consumptive purposes. Apart from that, Lazisnu Belitung also seeks to provide coaching and guidance in its implementation by the authorities to develop a productive business.